MONITORING OF THE FINANCIAL STATE OF PJSC “ZAPORIZHSTAL” AS A MECHANISM FOR INCREASING THE EFFICIENCY OF MANAGEMENT - Melikhova, Tetyana; Makarenko, Andriy; Melikhov, Yevgenii; Skachkova, Ksenia (Scientific Journal "Metallurgy", 2024)
Metallurgy is traditionally a basic branch of industry and plays an important role in the economy of Ukraine as a supplier of basic construction materials and an indicator of the country's socioeconomic development. Therefore, the research topic is very relevant for the economy of Ukraine. The state and trends of the development of metallurgy in Ukraine are analyzed. The main problems of the metallurgical industry of Ukraine are: a decrease in the share of the domestic market of Ukraine in the world volume of consumption of finished metal products, the growth of exports, which is connected with the surplus of steel products on the domestic market, the lack of innovations in the metallurgical industry, low investment activity. A financial analysis of the largest enterprise of the metallurgical industry of Ukraine was carried out PJSC "Zaporizhstal". Based on the analysis, the following suggestions are given for the development of metallurgical enterprises of Ukraine: attraction of foreign investors; attraction of additional cash flows of the founders through the revision of the dividend payment policy; modernization of the main production assets; review of product range; reduction of tax rates for metallurgical products when consumed in the domestic market; application of modern production technologies; reduction of sales for export of raw materials and semi-finished products. Based on the financial analysis, the following proposals are given for the development of metallurgical enterprises of Ukraine: attraction of foreign investors; attraction of additional cash flows of the founders through the revision of the dividend payment policy; modernization of the main production assets; review of product range; reduction of tax rates for metallurgical products when consumed in the domestic market; application of modern production technologies; reduction of sales for export of raw materials and semi-finished products.